Use of the Premix of Atrazine, Bicyclopyrone, S-Metolachlor, and Mesotrione for Weed Control in Corn (Zea mays L.): Herbicides used in corn production in Texas - Grichar, W. James; Nolte, Scott A.; Matocha, Matthew E.; Baumann, Paul; Bell, Jourdan M. (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
Field studies were conducted under conventional tillage from 2014 through the 2018 growing seasons in central, south-central, and the Panhandle regions of Texas to determine corn tolerance and weed efficacy of the four-way premix of atrazine plus bicyclopyrone plus mesotrione plus S-metolachlor (hereafter referred to as ABMS). No corn injury was noted at any location with any ABMS dose or application timing. Preemergence (PRE) applications of ABMS at 2.41 kg ha-1 controlled Palmer amaranth (Amaranthus palmeri S. Wats.) 73 to 100% while smellmelon (Cucumis melo L.) control was 100%. Annual sunflower (Helianthus annuus L.) control with ABMS at 2.41 kg ha-1 was 86% while a split application applied PRE followed by a postemergence (POST) application provided 99% control. Texas millet (Urochloa texana Buckl.) control with ABMS applied PRE ranged from 12 to 35% while broadleaf signalgrass (Brachiaria platyphylla [Griseb.] Nash) control was 100%. Browntop panicum [Urochloa fasciculate (Sw.) R. Webster] control with a PRE application of ABMS at 2.41 kg ai ha-1 was < 82% while jungle rice [Echinochloa colona (L.) Link] control was 98%. Control of a kochia (Kochia scoparia L.) with PRE applications of ABMS at 2.41 kg ha-1 was 95% while the split rate of 1.2 kg ha-1 applied PRE and POST provided 99% control. Corn yields were variable but in most instances all herbicide treatments improved yield over the untreated check. Excellent control of broadleaf weeds was observed with ABMS; however, annual grass control can be variable, especially with large-seeded annual grasses such as Texas millet.